STRATEGI KEBIJAKAN PERLINDUNGAN INVESTOR LOKAL DALAM ARUS BEBAS ASEAN ECONOMIC COMMUNITY - Nur Dewata, Mukti Fajar (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
ASEAN countries will enter the era of free trade through the agreement of Asean Economic Community Blueprint. This agreement will open the free flow of trade in goods, services, investment, capital and skilled labor. Regarding the investment, in particularly, all countries will apply the principles of the National Treatment and Most Favoured Nation. It means that all countries will give equal treatment between foreign investors and local investors. This poses a problem for Indonesian government on policy strategies to provide protection for local investors. This paper will use the normative juridical method for the discussion. However, to complete the analysis, empirical facts will also be carried to sharpen the argument. Based on the normative analysis, the result showed that Indonesian government has taken various strategies throughout legal instruments related to the investment law. Local investor protection is conducted by providing limits to the field of businesses, investment and divestment requirements for foreign investors.Keywords : policy strategies, asean economic community, local investor protection